Clusters as drivers of local industrial development in Egypt: Which are the promising sectors and locations? - Abdelaziz, Fatma; El-Enbaby, Hoda; Zhang, Xiaobo; Breisinger, Clemens (International Food Policy Research Institute, 2018)
Clusters – the geographic concentration of specialized firms that are working in similar or related activities and are interdependent – have played an important role in the industrial development of many countries, including in Europe, the Americas, and Asia. A large part of these successes can be explained by the ability of clusters to build on existing strengths of local communities, such as social capital and abundant labor, to overcome common constraints to economic expansion, such as weak financial markets and institutions. Realizing the potential for cluster-based development and the long history of clusters in the country, the Egyptian Government has made cluster-based industrialization a key pillar of Egypt’s sustainable development strategy to 2030. The timing for a cluster-based industrial development model for Egypt seems favorable as macroeconomic reforms in recent years have made Egypt’s economy more competitive and the country’s young labor force provides a comparative advantage for labor-intensive sectors. The objectives of this paper are to take stock of existing clusters in Egypt; to identify a set of promising “organic” clusters; and to make high-level recommendations for the further expansion of agribusiness and handicrafts clusters based on an innovative analysis of economic census data, a review of previous cluster studies in Egypt, and information obtained from expert interviews and a stakeholder workshop. Our findings suggest focusing cluster development efforts on Upper Egypt, which has a comparative advantage in several sectors, especially in labor-intensive sectors. However, the current cluster density in Upper Egypt is low, particularly in rural areas. Expanding the number and density of clusters there will likely require improvements in infrastructure, institutions, and services. The most promising clusters identified through the analysis include medical and aromatic plants, sugarcane, and tomatoes in the agribusiness sector; ready-made garments and carpets in the handicrafts sector, and furniture. These are all promising organic clusters based on their high market demand, export potential, labor intensity, and historical roots. We develop several recommendations for the agribusiness and the handicrafts sectors, especially highlighting the important facilitating role that local governments should play in cluster-based development by providing necessary basic public goods and services. In-depth case studies for specific, promising clusters should follow to help local governments and entrepreneurs to fully harness the unique opportunities that clusters can provide for local industrial development and job creation in Egypt.